Uji Patogenitas Jamur Cordyceps militaris L. terhadap Ulat Api (Setothosea asigna E.) (Lepidoptera : Limacodidae) di Rumah Kasa - Leo Alvian Ginting; Syahrial Oemry; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2015)
This study aims to study phatogenicity of C. militaris against S. asigna larvae in screen house. This study research using completely randomized design (CRD) nonfactorial with seven treatments and four replications, namely control, 10, 15, 20, 25, 30 and 35 grams C. militaris with corn media. The results showed that the application C. militaris in corn media was highly significant affected the mortality percentage of larvae S. asigna on obsevation four days after application and six days after the application. The highest mortality percentage on four days after application on C. militaris 35 gr (25%) and the lowest on C. militaris 10 grams (7.50%). The highest mortality percentage on six days after the application on C. militaris 35 grams, C. militaris 30 grams and C. militaris 25 grams (100%) and the lowest on C. militaris 10 grams (85%). Larvae S. asigna was infected by C. militaris suffered mimification and after afew days grow colonies colored white fungus (micelium) around the larva body.Keywords : Setothosea asigna, Cordyceps militaris, mortality percentage, corn media